Otwarte problemy w obszarze pedagogiki leczniczej - Hajnicz, Wanda; Konieczna, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Recently, it has been noticed that the problems of specific specializations in the field of special education overlap or go far beyond the area of a given sub-discipline. The article addresses issues related to outlining the main problems that we may encounter in the area of pedagogy, and which are crucial for the lives of people with chronic illness in various areas of their functioning. They are: body traits – their importance in building identity in the situation of experiencing a chronic disease; coping with loss in a chronic disease situation; matching in contact with a person with a chronic illness and participation in social exchange.